THE EFFECT OF ICE BREAKING STRATEGY MANAGEMENT ON STUDENTS' LEARNING CONCENTRATION IN LEARNING THE QUR'AN HADITH AT MTS ASSALAM TIMBUSENG - Andi Ati; Muhammad Yahya; Subehan Khalik (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
The concentration of students during learning often decreases due to monotonous teaching patterns, which creates a gap in practical strategies to sustain focus, particularly in Islamic education contexts. This research addresses that gap by examining ice-breaking management's role in enhancing students’ learning concentration in Al-Qur’an Hadis classes at MTs Assalam Timbuseng. The primary purpose of this study was to empirically test whether the application of structured ice-breaking strategies significantly influences students’ concentration during lessons. A quantitative approach with an ex-post facto design was applied. The population comprised all 58 seventh-grade students, who were included as the total sample. Data were collected through Likert-scale questionnaires and documentation, and the validity and reliability of the instrument were confirmed using Pearson correlation and Cronbach’s Alpha. Statistical analysis was conducted using simple linear regression through SPSS 25. The results indicate that ice-breaking strategies significantly positively affect learning concentration. The regression coefficient was positive, and the model was significant at p < 0.05, confirming that higher ice-breaking implementation correlates with increased concentration levels among students. These findings conclude that the research hypothesis is accepted, providing clear evidence that ice breaking is not merely an entertaining tool but a pedagogical strategy that enhances attention and engagement. Theoretically, the study reinforces learning and motivation theories emphasizing external stimuli, while practically, it offers applicable insights for teachers to create more dynamic, enjoyable, and effective classrooms in Islamic education.